Association Neutrophil Lymphocyte Ratio and Therapy Respons in Submandibular Abscess with and without Diabetes - Dian Ratna Chamora; Mohammad Dwijo Murdiyo; Iriana Maharani (PERHATI-KL, 2021)
ABSTRACTBackground: Submandibular abscess is one of the most common deep neck abscesses and associated with fatal complications which require adequate management. Diabetes mellitus (DM) is a chronic and complex disease that necessitates ongoing medical care with a multifactorial risk reduction strategy in addition to blood sugar control. The neutrophil lymphocyte ratio (NLR) is a simple marker for the systemic inflammatory conditions. An increased NLR values were found in patients with submandibular abscesses and patients with DM. Purpose: To determine the correlation between NLR to the therapeutic response of patients with submandibular abscesses with and without DM. Method: A cross-sectional study design with secondary data collection from medical records of submandibular abscess patients with and without DM. NLR value was compared between two groups. Correlation between NLR value and therapeutic response was compared between DM and non DM group. Result: The mean NLR of patients with and without DM were respectively 7.65 ± 4.92 and 16.53 ± 11. There was no significant difference between NLR and good therapeutic response or not in submandibular abscess patients with and without DM (p > 0.05). Conclusion: NLR of submandibular abscess patients with DM was lower than without DM. A lower NLR in submandibular abscess patients with DM did not have better response to therapy. Lower LNR in submandibular abscess patients without DM had a better therapeutic response, but it was not statistically significant.Keywords: neutrophil lymphocyte ratio, response to therapy, submandibular abscess, diabetes mellitusABSTRAKLatar belakang: Abses submandibula merupakan salah satu abses leher dalam yang paling sering ditemui dan berkaitan dengan komplikasi yang fatal sehingga diperlukan penatalaksanaan yang memadai pada pasien. Diabetes mellitus (DM) merupakan penyakit kronis dan kompleks, yang memerlukan perawatan medis berkelanjutan dengan strategi mengurangi risiko multifaktorial selain kontrol gula darah. Rasio neutrofil limfosit (RNL) merupakan penanda sederhana adanya kondisi inflamasi sistemik. Peningkatan nilai RNL ditemukan pada pasien dengan abses submandibula dan pasien DM. Tujuan: Mengetahui hubungan RNL terhadap respon terapi penderita abses submandibula dengan DM dan tanpa DM. Metode: Penelitian cross-sectional, sampel penelitian dari arsip rekam medis rawat inap pasien dengan diagnosis abses submandibula baik dengan komorbid DM dan tanpa komorbid DM. Nilai RNL dibandingkan diantara kedua kelompok. Hubungan nilai RNL dan respon terapi dibandingkan diantara kelompok DM dan tanpa DM. Hasil: Rerata nilai RNL pada pasien abses submandibula dengan komorbid DM sebesar 7,65 + 4,92 dan pada pasien tanpa komorbid DM sebesar 16,53 + 11. Tidak ada perbedaan yang signifikan antara nilai RNL terhadap respon terapi baik dan tidak baik pada pasien abses submandibula dengan komorbid DM dan tanpa DM (p>0,05). Kesimpulan: RNL penderita abses submandibula dengan DM lebih rendah daripada penderita tanpa DM. RNL yang lebih rendah tidak memiliki respon terapi yang lebih baik pada penderita abses submandibula dengan DM. RNL yang lebih rendah memiliki respon terapi yang lebih baik pada penderita abses submandibula tanpa DM, namun tidak bermakna secara statisitik.Kata kunci: rasio neutrofil limfosit, respon terapi, abses submandibula, diabetes mellitus